PERANCANGAN DAN IMPLEMENTASI CHIP FAST MULTIPLIER TRACHTENBERG METODE DUA JARI DENGAN BAHASA PEMROGRAMAN PERANGKAT KERAS AHDL PADA EPF10K30ETC144-1 - Thomas, Thomas (Jurnal Teknik Elektro, 2004)
This paper focuses on the process of designing and implementation of fast multiplier chipusing Trachtenberg method that is usually used for fast arithmetic computation in learningcalculation. By combining fast Trachtenberg method and fast hardware implementation insilicon chip, the faster multiplier will be produced. The performance of multiplier is essentialpart in determining the performance of digital signal processing system. In the era of digitalsystem nowadays, it needs the faster signal processing system due to the massive data to beprocessed especially in the real time system. The process of chip design initiates withdesigning all modules needed to build the fast multiplier chip. After all the modules workproperly by simulated verification, all the modules will be combined together to create thefast multiplier chip. There are two Trachtenberg methods, they are direct method and twofinger method. In this paper, Trachtenberg Two Finger method is used for designing of fastmultiplier on the EPF10K30ETC144-1 target device in AHDL (Altera Hardware DescriptionLanguage) code. Based on the results of the verification process, Trachtenberg two fingermethod fast multiplier can work properly in 27.47 MHz maximum speed using 76 % of thetarget device.Keywords: Design, implementation, fast, multiplier, Trachtenberg, chip, Two Finger metho